4 Διαμόρφωση πλάτους (Α.Μ.). D.S.B. (Διπλής πλευρικής ζώνης) - Ιωάννης Βανδίκας (ΤΕΙ Δυτικής Μακεδονίας, 2015)
: Good medicine almost gun mission Meta condemned to us that the TSP sin vOm mode for seat am didn't do is really am I flew through the mobile Mason Yeah most Schick a blockage did this great door while double-sided but view view more forces ina Mielle cystic operatives for the spring woman is going over it Yelich Crimson lip name as people have accused Sunni but Brooke let me pick for me I am issing that this would come as a super woman in my asthma debated a few months Mudd you got Yeah for sure I am Vinny deputies hison very am ISIL dices O'Farrell it pays Thoros GOP they have seen with San use all the tools Adam socialist guided all Blue is the you see look at that Yeah of course it was a mobilization goal rub shoulders with some mattresses must we need both said on Zazi pushing up we but you get everybody's phone love field divisive he's grown up but an enormous ACA divorce up got to eamon view no official for school safety most kids gave me before I don't inaudible Yeah I was deal but I'm in this for me for I'm a Federalist bomber to got to be able to keep get Tester Yeah more forces that are Fed up and pursuing middle GOP AFC meal the famed to doff git E affair this must end got a libertine involved two 0 zest a me own course 0 Pfc mussini to bottle liberty black explode out of view ocean my dorm email I'm not no we should maybe but maybe I don't know if he both said on did Domingo Yeah but you got to lubricate euphemism for about a month musician Pharrell emit salute these excellent pickup over lots of blood that opinion of luck initial Salem because for the 5 times notably Vicki because for them but together we have to keep fishermen Yes super fossil meant not for those from the bomb Russian-made cities with a we he to me MMA Casamance me come look at this look kissing for number two short years disaster since thus the is shovel ople mid cap fans make me give men kissing couple novice kids pieces look but added we have pictures of kids Here's basis you can maintain maintain their animated kids available forces there Sam flex Huish mission for number two Let's see ople Mitik Thins Let's make it a couple other steps Jenna to predict mouth told a fellow violent than ever shown his don't feel still but as my mostly by actually be America Bayonne devotion to secure this settled you know particular kids kid VMware forcing ople the vehicle some kids will get you look kids booked some products fee enough last month Brooks humane ople a view he nervous but listened as a kilo kids defend mixes you know should be given a chance or pushes a homeless woman Muslim looked beautiful 48 fights W given a deep it but by a live keep then by it's going make them we'll get the view should month Yeah you must get our Vonn who hoard of quarters not got to give it to you live for it male blow allusion Yeah we wish got maybe just wishing my love me moral cannot appear to be even more to got to give it a squad of deep Yeah I come up with the almost should give up bottom two beautiful would have put there's almost doesn't talk michigan needs Kimmel peers according to me this is continue he's getting get out of a bushel may go up to see me so much we should want me impurity jeff Bowman that yet you do have to keep boredom CNS vessels of most quickly got giant beautifully mast liverpool gunman picks going initial flash mob movie Steve we've had predicted the borders Horseshoe view stuff meet quick label opted to live ET Joshi and stuff most click them am is a good to have you Joan because some of them will glowed Nixon wanted baby short the stock maet court Ashley you last month obviously knew me wanted to deliver Hirsch sean this progressive stuff will I asked some movement do Nvidia the nothing neat when Ballmer knees his it's me could deliver launch just must give you scarcely distressed slowly within his bushy fast food resources at this sucked up by the had beat cope beat them but never saw this I missed the get someone to Wilson Mueller handed over those immune to keep us for evil places like me the shifting consumer of keeping up with the most Yeah I got the solution than normal being a bit month could slipping off the salutes when others Neil this if women instrument a member that uncle date emily the defense zeros mystic Yep a lot of fool Seema Mehta kids get a block of these Damore pushes so candid advice to protect we'll leave it on ever since the news kilobytes the most wanted to just be minustah Dov Lipman said festival she mostly by Hugh these solutions there are more ferocious as those tough admitted that gets people look at me sieve for official use such is even there's a kids it will prove it to cut tough stuff from the Committee just pick up above this kids 50 you don't it may theaters misses a blood test failed than have it when this refuge for bottle you did issue a city that is one of us Dinneen said using drugs at a bloom restroom own the blockage sting the thing to remember so I knew we pull Joshi well brooke when I got to make its position on the family's wanted them Medica said scape seniors enemy jkins and on Monday it will look to them to protect from limits I asked those vacate the to feminists would like to see it sold on to me up I'm naive Taiex hoarseness by 7 in ct it's worsened a deep pushed to the edge of buying less meat chili but 0 allowed by keep Burak alsos middle slows me Wilson said to avoid lip making simple game Bush Mitchell Yeah like a device theft from a vehicle she brings the total to my own Msey Vick at this polling makes this the more Torruella blood with a middle must sit own semiconductor depiction of this move for this border a bided their unbeaten shades to wt yet own certainly the miracle Oklahoma most thought a huge Vick episodes like you before those within missile like avoid thirst for shares giving giving me kid it pushing very important shops talk about enacted there's a if the Committee is one of the he'd see his repaid the federal it's just a Bull's eye to sicken or kill when Dominic Blue Taiex lost a few English the psych you this Acheson just over these fast food the top bottom thought out bull Mitt Mitt Mitt Mitt Mitt making Bessie born Lucius get do it is missy ople lavish unit giving members support wished I do not think it in we get it from the somewhat obvious start of Duke today if I'm more disappointed you Yes and he fashioned woman asks me all the men but Blatt boost Schumer a bottom in his signature move the avid U-verse kid AC I'm there's total Romanoff a focus of his body Cam me use bathrooms see my let me touch me's most of all the skill Lombardo Yes and Abby got cushions keep this or the masks the blood of movie it's a Matheson Munich will be key staff after ocean go low Bumi Bunning's deep but not putting Mitchell because a lot of momentum from the bottom up only said that his editor OSU's Jeff Roorda vl more push-ups with emotion ATM autism she loved them easy dish never gives yet much of one specific case bases beat you but that will be a little memorable meal option X I wish you the best finishing the conductor would go up but this is U up to shake together every day yet and expletive Yeah won't body she interview legislative mineral meet the potential Muslim men thought to date there wasn't just come let me give me 6 weeks two wins from two women the club Shasta boom Opel scott I love what you see is but it mouth Sonderman mm X with the sequel sequel much I love to take aluminum cans or could this give us a thought I moved me optional zeal Felix and conduct a skid can name showed up ocean Manson store looking at mental development it Kim is busy come us X within because these Shia incent right at me she wrote a much different Viser this picture David Koepp commute to contain NAUP Lumet storm misstated part of the gets up repeat cases was hit give them more ammo to boredom and upticks in believe Joe take won't put up with Jackson men make I think this team Mike ecial oral Utash's remember kicking Unix of fauna hinged Toyota's wanted total which benefits this the Bumble raffle yet we could lay the final push it's ocean bottom kept his wits the skills would get divorced she thinks this is the World you latest want border listen this emphasis communiqu Jetta gimmick family too she lumped with means mood his image he didn't have put up put it in a match this me you better Eamonn Mallie we risk among the view there is his relationship with or appreciate it thank you with the football alone for today which has can best is secured to a passionate push must defend UNC in addition to she led me to today Acosta Kucik would pave Simmons hits What Is The professional image Cupp but I Yeah we love you get to ask some the course CMMI kids we scrub looking typical Tom take told Lanza Domenico Scala into the vehicle summits Apple Columbus it was summits and boredom bottom do you hear he's shifting kidnapped boredom with can rush keep dropping kidnapped Kosinski President ING Jemele look at that for the innovate this is foolish political Islam asleep we use them if there was some of the slumber with the image it is coming up in the middle of I still email father Murphy former Bloomberg Let's give Russian because someone not all local into some triple don't want Nobilo but I think the thing we wish if the mean that and admits to the ball if the mean that intimate yet civic goals for you jimbo I live coming up in the middle of a if your goal go Mike that was a bull profane person you willingly in the West and that made me reporting major Yeah did a varsity he'd done it doesn't put an but we made it out I give them facing noon that success Yemen could this give us the keep the SBA loans still being debated should we got to get general Mills left Turkey is to make pushed him to slip through we just can't ask will be removed amid a legal document must view me that I asked him it medical mighty to skid as it lets you seem within the 15 Neil Oceana meals Sluman Domenico Scala ranch lipid kisses civility or meets with them enemies Helen Lom the jitters you can buy a bottle we need guns said this this I'm bombing but I was sick with this it kept pumping Dominicans vehicles couple been limiting kids told me could skew machine it zoom it's a lumber to defame him more use things thank you for Justice mediators from the disaster victim of shaking IEP uses system Gov bill was restricted to tipping the couple filed with 11 because since in excellent can grow let me get me a vetted with body T waking me which thing they have to start eat I'm glad we did get a question we give people been ruined because of something this Hue things pick up stuff almost you threw the ball well and some of the forgiveness the future Bob she has got us give us a minu teen use me love it Yeah a slippery pushing it lined up for thing it took a long been they've got to stop your she totaling about two one Egypt Schick kept pumping them make AG Lynch hopefully you bet if Mitt but if you're 60 he's hoping to make Kiley the McCluskey Welch if game mean girls Steele met a two columns of the thing most indicative for makes your aching reckoning within or someone you teammate since again dismissing was Mecca together it did someone aborted some people yet but I PMU get us but when you say left acute Opel or so sick of sticking it to them I could mention me your memories but here someone put it me I'm Fed up and they could stall I T you're asking what this to secure quotas Yeah put a punish them herself Mo Russians Sherman tends to let sell stuff Michael Bay's or we didn't suffer any something Lama Simango us thought it receptionist Shlomo we should just 13 to Or Snowe says that most people 58 will be even if it wasn't for been indicative but Anderson you open your blog zippo people won't implement pitting ethnic in Minneapolis city get out what McCaskill state reported coming locals Kimmitt collection replica of lower election gives the deficit is Zen with a lovely he's young he's giving him a couple of the flipping number caption Oakland but I'm with yet but I've Yeah for sure never scared there to zip along in the staff member Gemma T photo Myers the key should be cool make they beat you needed to avoid a shows there's less doesn't I'm with two of the polling after seeing me Monica all of and his defense Bush a final push like got to looks there's a performs at this for the two of you ople people you didn't Yes fair a wicket knees yet ceiling take that for what if you could only Miller it's a little bit in the vote get anything such fare a you don't do through Monday the co-president but I CDs lip balm to personas Disney feces museum staff Simonton if I look forced upon the muscle it's a police state but I think this boredom enough bombs kept true I moved people to meal I'm 60 years should but his was the most difficult after human thing make skeptics normally scanning this he goes to this gang teen opt-in Yep Liz thank you so communities your prayers devices it said I'm dressed theater we but he will be short marriage because people Kissel personal matters one number captain at the St. duties you'll be able to men and less Mahlum Ganim Yes you keep it showed that funeral if not debated push one recklessly initial very Mohsin Yes it was this again I'm I like to see mother Zuma you get a wishing me a live up I asked he did that or pushing the Monica voter son position what do you do that expenditure Simba up often the movement to put up with this so low on the list that Vinnik embassy asked both for special do you East Houston up woo enough see official but we're not you get after you wouldn't think make guided the epilepsy up adopt rules it will top of the World trade gap put up pickle say would you put on a missile they can put sufficient this get this Yeah I thought I should too divided to Anna good to see you vessel defender did do good graphics this suited to couples were enough elements to the garbage I think Walsh's group will move size at the also appeals to me I'd gotten to the commit to avoid Yeah Stone washed them bottom but economy it also kyushu makes its way here a missed shot up to deal with that huge Big time rush across this city Victor some love ya think this up into the upper body if you can he did that for a Moos make that a team D ople love to sue the NBA the DB or persecution to equal the almost nothing pulls people putting that option was not yet suing dn't fought out too but I keep go see my son me straight surely is BS us justices asked us Vicente those Florida they showed us Yeah meal lamented missing the second avoid this after peaceful up upon me to got to manage kiss good normal this gosh just your normal definitely and then e've but the BIA the studio's Manafort a should complete goals able echoes of gng if he'd get a lot of people museum I lays out all man appeal victim to scan for this mission we heaviest thats the potive slayings sleeved T mostly is loving it tip sets fire to put Let's get the thing that Apple to fellow Vine jumper to take them unless we estimate that it will be skin which Plano West coast Hubert and allows me option mid mysterious Cecil ocean Neil in need someone get aching me SE for Hindus this he can't have me S is good this is a gun laws deal cumin scented candles or victims he don't most but they will stay seems to me to assist the Munich get down Yeah would depend veterans before totals for Bush's pick for one of those people who hated it absolutely will put him may is looming up to give them up because of a isn't up to the site yet Schick a bombing victims we've yet to fly BFM it's I'm fighting for today of course we shook up only two hits column of Guinea today I met a alone but that the 58 if them up because you get like this device that's getting to I applaud you for us filling the deal meantime Here's an option you social I applaud the menial molested this I mean look this image it will mean nothing because like me he sees fit Yeah there's this thought goodbye you ask locals people email zooming up and they'll body was pulled taping a bottle McCullough is looming up dome reflects the evolution of this was an event to blame my buy stuff got to shield with a ballroom and really see today Nicole bite it's upon us here to report took a very sensitive this sieve women up dome tend to push 6 still bristle medics put your phone Pacific this is inmate take deep if coming up don't I hope did Dan upper subways you up together Yeah makes the ball ball it suspended the maze of additional uh Hello yet Slovenia in italy you're probably thinking get video listen if coming up don't hallmarks of nickel BLITZER candy most of us like I moved to get the Buck bureau to this I'm one of them together give it just look at 11 movement opposition got his stick that quakes Yes jim dement so they can then there's the family about picked that Gomez I will do what it should be up 40s Obokata's we'll pick up the middle of it could be up for use michigan 11 to date and that tells you to me she beat initiative to help with Tom Kissimmee social yet check out will there be a mid sing give us lessons juice unlike the Mets Yep we cuts he said him almost with decent at the end dismissive but keeping their needs yet together to book a room for us just a victim into mobile I'm not Let's really look cool but I would like to come we get the ball is it appealed to me anybody on the list the special like my standing with aviation yet doesn't mean you will team up to fun it's the only give me up and don't Bob from almost Yeah mysterious or abortion need serious table gunplay UPS it me and I still got a medal interest Huasun admitted that from govern just goes in motion you can't escape it seems so forget the less baby doll got low yield much but if the nation is this is baby doll he busted through ticker I mean he football Bowl me Lemon Jake for being to put a little but I have my turn Steve Dixon we've dusted the give finish the thought of a Government though the UK Coloma I'm not alone USEC full rate kidnapping home Carlos over the middle for us it bases being home mostly though may have placed the St think Here's it would to me he's with the Fortescue I don't he's just bite the bullet begins to get out Mitt that's it the same promoting equal Yuma take them dissipated while Yeah he'll pivot within the walls cynical she sleep someone Harvey was a limit we'll take you President credit so we need to keep from you this will be opened them up and man up rolling my some portion of music E go meet most steadfast look at that we get this month if Mudd absolutely I mean it will be sic up make active groups today Chicago because you want to study at column than ever levied against austere absolutely blown he toasted sealed quick payment but didn't give up and got to stop Yes Vanier coming up the Cup for you can't make it to me good it'll make us Venson uneasy get Yep Stacey Cook Cook won't bore mep within a month ease his prosperity when Bush was get made is that if you buy a Bowl hospital Mize the special month to month download postal system deal model heap the GM how do you then if Necas a Noble he sees Biden as beneficial but Rob it still interest will balk gambit Ashley got fast fast was the mother of Junaid would most like us after after living with it introduced the drama when normal passage I'm glad one I'm glad the McCann that's Brienne being op pointed to me she did this they got my Muslim total Joel Loew s star Simone you my own view is up just Here's a NSC role Z enemy young little it daily the debated closely in the name them one mouth up all alone off field loaded pushing venue with a bogey coming to me and the other than it got me I'm necklace Astorino depicting people just Bush fossil Mitt I'm doing a gunman so myself more Columbus numb his initial force unit did that's what I like the make don't keep Bessie bme Oakenfold disposable but easy because I assume we have basic or basic but took a side dish made it in to give us some cannot he's different FT email knowledge Donald convicted Steve makes a little more vivid finally coming so this after revolution you I'm let me get more of a tipping love I mean 02 glow mother gun it see if we take a these passes by bruce you get that plenty for us to Union me Yeah I mean for us keep us heap but viewing this if we take it best to put up with immunity the fencing he finished a man itself but in up with things people begin in normal while Lynch using an Apple to diminish the threat to the still-forming image Smith like Nick but Boeing is the Guinness Liberties informant he visited suffer this in this league demand as you get the seeker Brooke this was a different using the device in our little premature right all this the smoke the yet but as you but CJ if you don't live very civilian component they got only you grew up with a thumping of the Yankees will utility for me for me thought of the victim think his give her this Yep part of my people you can we sit down with us versus give the edge immuno that's 5 to get money keep keep bending amid again tip things together enough to vote I'm finished with the best fight keep investors if Mmmm low hope Yeah would refund state said Neil Saunders daughter Jenna supposition signed skin the other Bunny will spend divided Stephenville here it's a little beep but you'll sellers if his vehicle this wasn't good simple 10% I mean in a sham a so maybe than it got me on that policy in an initial thank you permission enough persevere kissing the social index options available for Lama or have a team to renew ople stressing that the tip by unknown innocent the social cooking of the VA is a memo yet supported I'm equal the stream buying opportunity mobile numbers today doe't stop mother begins it will be you lives lookups phone mobile look this may have thought he you're the British wouldn't you like to go stay I mean his agenda you've kept cool and McGahn Comey could probably never week efficient missed a selfish what scares he's sucking up bikes get tips if you thought that candid exhibit s total when President Bush took a selfie he soon to be ex will goes if listed beam you scream but you she's the if she didn't get their loved one Suma Get sample more bullish did you get a but follow the metallic yeses today Here's what you missed me don't ocean Yes blow one skit on Jewish impotent uses that's strongly go along you can listen to them for gets a little to show Steve it seems as if a Government or use only throw you you will point it's showing the does Russia quickly they need but proportional inside feet winnings to the name because federal he and Schumer well we love it in because I hope when she was a black things taken immunized Yeah love it seema miss Florida vote by Russia that practice field those wings this Nick anyway you got a month not view for shift Toca cool to let me ask you misquoted formed by us but avoid this presumably to live after I think we've got to continue to see sit but not for the city to that love money to guide the total another she ople to get better wings official Vinson she didn't just give us us who just got me as a solution again my God I love it I receive Zendesk a Schumer I hope part of the two guys to skew the request Flake the guided the field testing equipment being name just debating destructive force for frankly has in win blew us most I blow up we DeVos from making the District court to Sunlen let me be me have vested den DO us you do something for those principles spite this investment you're innocent give lower descriptive due to the shortest I'll get to you that is new to the children's Here's London's can Stuart love team to keep it ruined my you only injecting it won't be yelled you can and will beat you by for people pieces have been all national in no he debt needed see part two will be sent stiffened up though ida eat it Penton I'm kind of vehicle me God of Slovenia didn'know us nd it's did take a listen infection risk of them up adult I've got news exclusively reported pitches give little make home be put upon them maybe they don't come them sure he's definition feel I just miss unicorn persistently lost a bid to unequal yet T East we've got us beloved I'm to get Yeah votings T whose vehicle level this lek als a bunch push cash but Here's you but officials in Cooper OK Yeah big take dispute which tells you Ocean lakes state news don't make much in policing is a diplomate examined as multiple units respond total good lessons you think we've got a quota within minutes of the official his number that techie Kwon after unit Brazil's ferocious kind of solution kind spirit to scuttle playoff bound book ends up doing that it's good this is you love your mother I am used to use all should definitely alive given by you cannot fix the Gorsuch sympathetic of the the one with the listing of the within we just grown values these for us no because of this and who did it together some night which take a look here you think we have a if boy listen this like Olivia reminded it's up to you wish IHOP for take us through this kind of X I will show you the singular lessons in front by the ELA facility dresses the thickest much Moulton because special which is still a big fall what's sick uploaded by moon with an official then rush going if the judgment the month more with but for America it begins with a woman kissing up available she hit the got love for body got his Ms. seema am is abused children Tyshaun's but it almost kept his lead walk about this let all the more she gonna we should be beautifully quick payment Jenna you know spoke cesium for stadium up it can feel like your girl look at this you must Apple's deals Temple pursuant to if you push if it's slipping to 50 K video of it was lit it up get dical meaning the applicable Roma looking at buying up physical maybe ineffective kicking me the best mixed 14 it got of the woman had to push the finish if repeal mess-up after Schumer making use of the limit accents clears some of those of you watching women make goods victory as like the sort of the abortion question either the film certainly for ople it was mechanical skill kids getting vetted I mean it takes this look at that Phoenix octaves eve up blouse worn ask vices to have me Yeah of course I happen not to seem risky here it's going to mean see you tomorrow except the border most can after the game produced hoping to succeed scored just he'd do yourself a few drama 01 economy our kids interests having missed the we new media I seem to put them personages given the tone better fish in NYC to defeat the Apollo 11 chess that we're bombing Shi' ites active Bush you by your motion must persuade invective stimulus for the new good too late he said usual aim vs Romania fix-it Omega Izzo stick you go much if Zuma that yet Israel may it hit them Omega view be if mid lands and made him it's I don't I felt almost as old give me Kim if becoming this group of Justice through the volume is all he's a part of one must up with this I kids taking them in just a minute to that effect which hits I don't live within oil made a motion to make that point immigrant for the thought was opposite position would simply make and boarded them the PX the mask will on people timid this through this he said I think someone I'm picking a team up Harlow Yes instead of acquisitions slave may I have just said got to keep all just time it hits limit he home you don't States you born into a loving it Let's and because the Stoneman MP next miss to board the values of liberal is somebody's people he's definitely hits them make ego all old I'm just listen tgif keep Egypt on becoming mature ability against Phil Texas few low Homeland this is fix which left a thanks joining just a definite PNAS senior official Gus official most ings you can separate quotient of Jim unless we get a woman to beautifully it does none pushed them because what here next will committed to she is it's new to us a farming community Nixon supple me but I've become a pickup on slot on stay perspective was about is folks he may use the special one of this proportion voter intimidation shovel because a big S back I want to doping through this but 9 days to go see it it's equipped with after the best Smith and pick with this computer before if this was beuse 6 look at what he likes me game we get through this it's taken on a couple of hot on in 6 of the devil we we make anything you Tester World equity equal after dash left his initial the effect of innovative solutions then refused make early the passage of the need to go Zamili backs program meco city by two one you can believe that Jozy it's cool picking team mascots and get within that move mission from edge in addition it's I was really Sumbal especial liking a brief on this we get the ball ball boy Romans I'm dismayed at the Egyptian Yemen kind to me this is war Yeah form bull enemies would afford us take demands timid fish we keep a special my key 5 5 deepest therefore easiest hook that being the good us un unity team if they get a stick-up living meeting then it kind of got us to this invest from because neither of us sting Nixon Bolivian food store down it opened the summit Yes a make insist assuming you battle sting the option Jen let me get you to cater for guess mother he bison too busy omits will feel levels finally thesee mother boredom with us doing this Mississippi could be men know got knighted Nov Ltd a deal that I'm sure for you get the the official that the deal with a vs a total phony Yeah nothing it moved to the token you kill them with everything in this crucial month of Cindy meet me girl vault submissive Yeah get us lessons me today the FT Jimmy to beautifully it had me it kindly Cuomo flipping nice Yes that's a good thing that makes the you go vote to buy which got the Boston punted on this you'll get this you we love you brooke jeff there's no mika excess and sleep you seem to think he did much to test but is this it will just say that Let's move from the adult you get me execute bathrooms you do it sick after 10 months tiny by giving up don't Yeah that much is thought it to be didn't notice into them Dan what's what's one thing you need Altena makes those things I think it's just Let's I was really shameless we took a little Calais is Fortunately the name if Syrian likened to attend the school is what it is and you watching weekek Loza hallmarks of the kind that would be the only auctioned Emma physical got those are your your blatant I am voting for Mitt Let's call this what it viewed the tick I wasn't border remain nik haley dropped a vestige of the that pushes them Inc version does feel equal Jessen courses it's just like with the this who this man is the theater's t's the municipal appointments is young nominal Lexuses within this this gunman governments feel I've still got a police force you the school million we do palms together Suski lived with many you have to together to its caption disappoints somewhat amused at the Ocean off of that kind of an indicator one local within a minute of soon this index if this stuff teen easier for completing the point is that at this soprano whoosh should put a boost to get the message women's GM management if the spoke after a group of fixes fibula the Tanaka we women Yeah I'm people out here in but Here's a bit of a management Upton hit a key it Bowman no but is it all no but isn't to affix his execution seemed like one of my it needs to be me girl holds is based on your part of the it's a means it seemed humans if anything they sign on that I mean me Lemon Yep your force equals a man's care after she made a deal with diplomacy me up with a brave woman no could use the tool will return to visit I'm not going to do if they wish there's this AFT pieces were you guys up bonus chilling isn't it I think development will use classical miss I he's if a chemical that get them it's just the Munich to mock would think divisive but up to human to do prevent promo you Samira I meet emissions it reportedly told sends solution listen I've maybe we're too stupid or too they almost can't abuse give social news it enough on movement the spot shifted to more Nava mental we definitely need to develop this made sense and we have is a leftist revolution meal you don't dislike both of them you won't mean something you get this there it is it's got us us just think music Nashville McCloskey modest portion the to me Stuart the mid game Yeah gunman Erickson Manafort on israel they get us ties to finish people may get an opposition motion to I asked him to make our appeal victim a quick anything am Jim Wilson product we need these LCD display rumors they K D this include usual school he told me if we meet up with the most to the newsroom the probe by this Vick hts you getit he assumed the most should be the cement bottom bottom bottom boarded it he one number of shipping shortage what this guided the tribute to a it who tissue violence connected to them for sure am Vinson another Olynyk celebrities he's won a total is almost shook with me salute I wish I them University justices I'm officially stadium kid D is being cut a lot of kids police blew a kiss Sean means 8 meeting one of the abuse of Fusion was doing thanks said previously in limbo dish on and my hazy glow dizzy most should Grossman unit today who did a up to maine now opec that one little versus Lynch Lynch said that the Sunday exceed Blatt hazy Azam Foreman motion Mike innocently skittish guys if pollution hopelessness to zooming having this month after going through its own and immigrant kids up want to ensure Muslim men died on the date wish more another women Americans were on the part of me just only defined we'll gunmen up biting moan to victims still mix Toobin it is the most Shi am got a lot of final got a couple of key did both said on opioid I'm hugely Oceania he should use less seemly steam Dima got reason Goma Fame day Meeker Saquon he did you listen to that aim the zeal of like hippie musical mopping Dimick Strickland and consequent and let the sickest Munich the enemy is the bomb for glass might give that animated hits or in the case Holder percentage we should of course militants could devise a bushel motion have meetings look at them for leave question to ask them if Mitt come look for instance she's only born to more Nava zoom they still too close to call dismissed with Schutz said it it's your state let me amazingly he's looking noted that who most people gives us a little bit which suggests again welcome to assist ocean must receive eat I'm in using a phone ocean little coming look at it come look just starts pushing mud ocean excuse me him gold Bumble with estimates of Emmett team she multitask retooling it animated hits plus told Musto zMe up to Russia you get somebody opening she zoomed can you do that if you want to you musicianship it they devote time division keep instead of letting that social guided mostly sting Mitchell it is more of a vitamin C my enemy the hits keep love like hope Hicks the XTC you can't allow vomit made two races means afforded just look this ople do you need to get him more ferocious bringing here you need to come to tone love understood miss Apple and my kids dependent both picked the big jennifer's english should there's a sense kid been divorced with two big jim they had to do this it's your state my boardroom it apart happens we can limit them Eskimo from Trish hinged upon moving off tools still managed to get out a bunch of Russian Malcolm Mitchell to dish will deter Zimmerman two tackles kids men this victim got more and than of the Muslim make up with a couple take it off on the seas with dish just appropriate among J Meadows Mr. cool said someone believe shown spokeswoman that's mission or a stay of execution for dish thenly reason or the CBF ball he's tasked with evolution he's he's a chill we meet them quizzical love by to stream To make up for the VP's delivered just and support the notion summit got a blockage did his views on his tip for total mess with my get diversion Moreno a view of the kiss crucial so Osteen Yes this cover live devices she became one of the index in French occasionally to Shaquem secluded on this clues can be humanly impossible for the deceiving Mitt didn't she wrote them off for much tests